Cognitive Flexibility as A Moderating Role for Gratitude and Depression in Individuals Who Lost Their Jobs - Temmy Andreas Habibie; Fuad Nashori (Indigenous: Jurnal Ilmiah Psikologi, 2024)
This study aims to examine the moderating role of cognitive flexibility in the effect of gratitude on depression in individuals who have lost their jobs. A total of 216 respondents (male = 188, female = 28) from various regions in Indonesia participated in this study through purposive sampling technique. In this study, three psychological scales were used including gratitude scale (α = 0.947), depression subtest of the DASS-42 (α = 0.933), and cognitive flexibility inventory (α = 0.794). Moderation analysis revealed that cognitive flexibility played an important role in reducing depression (β = -0.121; p = 0.041), while gratitude did not show a significant role in reducing depression (β = 0.005; p = 0.947). Cognitive flexibility plays a role in reducing depression, regardless of the level of gratitude of individuals who have lost their jobs.